Metaverse Marketing: A Business-To-Business Analysis of Brand Strategies and Generation Z Engagement in the Sports Industry - Saima Hussain; Rizwan Raheem Ahmed; Dalia Streimikiene; Faheem Bukhari; Justas Streimikis (Amfiteatru Economic)
This research explores the interplay between the services the Metaverse industry provides, including brand gamification, Metaverse marketing factors (novelty, interactivity, Influencer), and their impact on brand advocacy and loyalty among Generation Z within the sports industry. Employing a quantitative approach, the researchers collected data from 384 participants. The findings reveal significant positive relationships between brand gamification and Metaverse novelty and interactivity. The outcomes of Metaverse devices exhibited that consumers developed a strong affinity for specific brands due to the influence of social media influencers. In addition, the vibrant and dynamic realm of the Metaverse has generated a wave of positive brand sentiment among individuals. The research examined the efficiency of transforming brand experiences inside the Metaverse into gamified systems, significantly influencing people and increasing their affection for the brands within the sports industry. Metaverse is a critical tool for Generation Z as this group seeks immersive, active, and engaging experiences, and effective branding in Metaverse can provide a solid appeal to this tech-savvy youth. The findings of this research provide significant managerial implications for both the Metaverse market and the sports industry, highlighting the significance of leveraging the Metaverse for enhanced brand engagement and loyalty among Generation Z.